A Sharp View on River Dune Transition to Upper Stage Plane Bed. Issue 22 (23rd November 2017) - Naqshband, S.; Hoitink, A. J. F.; McElroy, B.; Hurther, D.; Hulscher, S. J. M. H.
Abstract: Sandy river beds are dominated by rhythmic features known as dunes. Experimental investigations of turbulent flow and sediment transport over dunes have predominantly focused on equilibrium flows that are rare in natural rivers. Using a novel acoustic instrument over migrating dunes in a laboratory setting, we quantify a number of dynamical properties that are crucial in our understanding and modeling of dune morphology and kinematics, particularly under nonequilibrium flows during dune transition to upper stage plane bed. Measured sediment transport distributions reveal a positive spatial lag between dune crest and maximum sediment transport rate that eventually caused washing out of dunes. Bed load was entirely captured in dune troughs, contributing to dune translation where most of suspended load was advected further downstream contributing to dune deformation. Measured bypass fraction was about 76%, which means that only 24% of the total sediment load at the dune crest contributed to dune migration. Key Points: Flow separation zone behind dunes differs between equilibrium and nonequilibrium flow conditions Sediment transport reveals positive lag between dune crest and maximum sediment transport during dune transition to upper stage plane bed An extremely high bypass fraction causes a sediment deficit in dunes that eventually leads to washing out of dunes